Peningkatan Kompetensi Manajerial Petani Kopi untuk Pengembangan Wisata Agraris â€œLodjiâ€ Bromo - Lilik Wahyuni; Muhammad Hambali; Maulfi Syaiful Rizal; Kiki Fibrianto; Igoy Aryo Bimo; Khalid Rahman (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service activity aims to enhance coffee farmersâ€™ managerial competence in Wonorejo Village, Pasuruan Regency, in their efforts to develop agritourism at Bromo's 'Lodji.' The implementation method of this community service involves socialization through location service identification, brainstorming, and group discussions. The evaluation instrument for this activity utilizes surveys and is analyzed descriptively. The results of this community service show that the socialization of coffee farming tourism has proven to be an effective means of developing the management capacity of farmers in various aspects, including self-management, business management, and teamwork. Through this socialization, farmers are provided with the knowledge and skills necessary to become effective managers in managing their coffee farms.